2016
DOI: 10.2196/jmir.5314
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Mental Health Apps for Aboriginal and Torres Strait Islander Australians: A Qualitative Study

Abstract: BackgroundAboriginal and Torres Strait Islander Australians experience high rates of mental illness and psychological distress compared to their non-Indigenous counterparts. E-mental health tools offer an opportunity for accessible, effective, and acceptable treatment. The AIMhi Stay Strong app and the ibobbly suicide prevention app are treatment tools designed to combat the disproportionately high levels of mental illness and stress experienced within the Aboriginal and Torres Strait Islander community.Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(202 citation statements)
references
References 25 publications
5
197
0
Order By: Relevance
“…Participants observed that SEWB interventions needed to be more accessible, with greater effort put into appropriate marketing, ensuring that community members were aware of initiatives (Povey et al, ), and creating safe environments. Inappropriate engagement strategies, including physical environments, language, communication methods and even visual imagery caused a disconnect; “They've got the paintings that don't culturally connect with Indigenous [people].…”
Section: Resultsmentioning
confidence: 99%
“…Participants observed that SEWB interventions needed to be more accessible, with greater effort put into appropriate marketing, ensuring that community members were aware of initiatives (Povey et al, ), and creating safe environments. Inappropriate engagement strategies, including physical environments, language, communication methods and even visual imagery caused a disconnect; “They've got the paintings that don't culturally connect with Indigenous [people].…”
Section: Resultsmentioning
confidence: 99%
“…To date, there has been limited research on the co-design and evaluation of culturally appropriate technology-based health approaches for older Aboriginal people. One study (29), explored Aboriginal experiences of using two e-mental health APPS, which were developed through extensive community consultation -the AIMhi Stay Strong APP and the ibobbly suicide prevention APP. Participants in these studies expressed strong support for the concept of an APP.…”
Section: Technology As a Platform For Program Deliverymentioning
confidence: 99%
“…The barrier of having lesser technical ability can be overcome by designing app characteristics, such as graphics and ease of use, to accommodate older people (29,68,69). When designed to support Aboriginal people's needs, technology-based health interventions could add an important element to improving the healthy ageing of Aboriginal people.…”
Section: Health Education and Empowermentmentioning
confidence: 99%
“…Fewer studies have been conducted with Indigenous populations; however a recent literature review of international studies suggests usefulness of eMH approaches for Indigenous populations, globally [7]. Similarly, ndings within Australia suggests that eMH approaches are perceived to be acceptable, feasible, and appropriate for Aboriginal and Torres Strait Islander people (the term Indigenous Australians is used hereafter; with acknowledgement and recognition of the diversity of Aboriginal and Torres Strait Islander languages and traditions), by both community members and service providers [8][9][10][11].…”
mentioning
confidence: 99%